Estrategias y políticas aplicadas por la compañía Translibertador S.A. para liderar el mercado de transporte escolar - Carvajal Poveda, Wilmer Lenin (2017)
Know the strategies that the Company Translibertador S.A is applying, in order to achieve its institutional objectives, which market share this company has, the services that the company providing in transportation are of highest quality and on the other hand users are satisfied with the service. With the analysis of this case it is wanted to know where there is difficulty or deviation of the application of the strategies used by the company, information that is used to apply correctly strategies in concordance with organizational objectives. The strategies applied by Company Translibertador S.A, were made undocumented, that’s way is not documented the serves as a guide for its application, to document the strategies in a file in the company to be used as a backup, to show which were the results achieved, and with these strategies to do a feedback to be able to reach the objectives set. The market share of Company Translibertador S.A., were analized, which offers the transportation service in the Central-North Sector of the Distrito Metropolitano de Quito, ther this information has allowed to know what user need in a personalized service.